Essential truths of the Christian faith - Sproul, Robert Charles, 1939- (Wheaton, IL Tyndale, 1992)
Includes bibliographical references and index.
Keywords: Theology, doctrinal -- popular works; Reformed church -- doctrines; Evangelicalism